2022
DOI: 10.3389/fphys.2022.787231
|View full text |Cite
|
Sign up to set email alerts
|

Airway Pressure Release Ventilation With Time-Controlled Adaptive Ventilation (TCAV™) in COVID-19: A Community Hospital’s Experience

Abstract: Santa Cabrini Ospedale, a community hospital in Montreal, Canada, used the airway pressure release ventilation following a time-controlled adaptive ventilation (APRV-TCAV™) approach for several patients in the first wave of the coronavirus disease 2019 (COVID-19) outbreak in the spring of 2021. Based on favorable patient responses, it became the primary mode of invasive mechanical ventilation—from initiation through extubation—during the second and third waves of COVID-19. In this article, we describe our succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In our previous study, the respiratory therapist started to perform the weaning protocol when patients achieved the criteria with a P-high of 20 cm H 2 O and F io 2 less than or equal to 40% ( 2 ). Rola and Daxon ( 3 ) reported that a COVID-19 patient started spontaneous breathing trial when P-high decreased to 22 cm H 2 O and recovered.…”
Section: To the Editormentioning
confidence: 99%
“…In our previous study, the respiratory therapist started to perform the weaning protocol when patients achieved the criteria with a P-high of 20 cm H 2 O and F io 2 less than or equal to 40% ( 2 ). Rola and Daxon ( 3 ) reported that a COVID-19 patient started spontaneous breathing trial when P-high decreased to 22 cm H 2 O and recovered.…”
Section: To the Editormentioning
confidence: 99%
“…We have previously demonstrated that if the expiratory flow is terminated (T EF ) at 75% of the peak expiratory flow (P EF ) (P EF L/min x 75% = T EF L/min), alveolar collapse and dynamic heterogeneity is prevented, whereas increasing the T Low (P EF x 10%, 25%, or 50%) does not. We have further shown that using this method to set T Low is highly lung-protective both in a clinically relevant large animal model and in clinical case series [40][41][42]. Despite the volume of data supporting its use, only one study included in our present analysis used P EF 75% to set the T Low [36].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, like any other mode, using APRV for the first time without a general understanding of the rationale and settings on a critically ill and unstable patient with severe ARDS who is failing ‘conventional therapies’ may not be as successful as when applied by providers who have experience and use it daily as their primary mechanical ventilation strategy. In actuality, APRV has already been used successfully on tens of thousands of patients for over 30 years and continues to be a part of daily care in many hospitals amassing a large amount of empirical data ( Sadowitz et al, 2011 ; Andrews et al, 2013b ; Mallory and Cheifetz, 2020 ; Rola and Daxon, 2022 ). It is understandable that users who have never actually used APRV or are unfamiliar with this way of thinking about mechanical ventilation may consider it too difficult ( Nieman et al, 2017a ; Nieman et al, 2017b ; Nieman et al, 2018b ; Nieman et al, 2020a ; Nieman et al, 2020b ).…”
Section: Myth #1—airway Pressure Release Ventilation Is Too Difficult...mentioning
confidence: 99%